2013
DOI: 10.1371/journal.pone.0067882
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Testis-Enriched Gene Spata33 Is Expressed during Spermatogenesis

Abstract: With an increasing incidence of male idiopathic infertility, identification of novel genes involved in spermatogenesis is an important aspect for the understanding of human testicular failure. In the present study, we have identified a novel gene Spata33, also called as 4732415M23Rik or C16orf55, which is conserved in mammalian species. Spata33 was predominantly expressed in the postpartum and adult mouse testes at mRNA and protein levels. Its expression was increased during the first wave of the spermatogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 37 publications
2
11
0
1
Order By: Relevance
“…The following pieces of evidence based on our immunohistochemistry results showed the expression of SPATA33 protein in spermatogonia, spermatocyte, and spermatid cells in the control group. This is in agreement with a former study that indicated that SPATA33 was predominantly expressed in the spermatocytes, spermatogonia, and round spermatids (Chen et al, 2013).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The following pieces of evidence based on our immunohistochemistry results showed the expression of SPATA33 protein in spermatogonia, spermatocyte, and spermatid cells in the control group. This is in agreement with a former study that indicated that SPATA33 was predominantly expressed in the spermatocytes, spermatogonia, and round spermatids (Chen et al, 2013).…”
Section: Discussionsupporting
confidence: 94%
“…From the gene expression point of view, in a previous research, in 2013, by Chen, a close relationship between the expression level of SPATA33 and the first spermatogenic wave in the mouse postnatal testis was illustrated (Chen et al, ). In agreement with Chen’s result, our data on the SPATA33 gene expression at the mRNA level in azoospermic patients, including patients with SCOS, MA, and HS (as the control group) revealed a significant decrease in the SPATA33 gene expression in the SCOS group compared with the MA and control groups.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Treatments for male infertility have not been developed as the associated molecular mechanisms are not well understood (2). A more detailed investigation of the physiological mechanisms of spermatogenesis is required for an improved understanding of infertility prior to the development of therapies for this condition.…”
Section: Introductionmentioning
confidence: 99%